Industrial Energy Consumption and Carbon Emission Decoupling Study and Driving Factor Analysis: A Case Study of Sichuan Province, China - Tang, Weiguo; Ding, Yi (International Journal of Natural Resources and Environmental Studies, 2025)
The carbon emission of industrial energy consumption has an important impact on a region's carbon emission reduction and optimization of carbon emission path. Based on the STIRPAT model and the TAPIO decoupling model, this study analyzes the driving factors and decoupling relationship between carbon emissions from industrial energy consumption and economic growth in Sichuan Province. The research shows that: (1) The industrial carbon emissions in Sichuan Province are increasing first and then decreasing, with an increase of 18.78% from 2005 to 2022, and the carbon emission intensity has decreased from 1.94 tons/10,000 yuan to 0.29 tons/10,000 yuan; (2) The decoupling relationship between industrial carbon emissions and economic growth in Sichuan Province presents three development periods, mainly strong decoupling and weak decoupling. According to the decomposition factors, the decoupling relationship between industrial carbon emissions and economic development is mainly affected by the decoupling coefficient of value creation and emission reduction; (3) The proportion of secondary industry, the number of industrial enterprises, and the total industrial assets are the main carbon promoting factors of industrial carbon emission in Sichuan Province, with elastic coefficients of 0.097, 0.057 and 0.040 respectively; population size is a carbon reduction factor with an elastic coefficient of -0.087. Finally, the study puts forward some suggestions to realize industrial carbon emission reduction.